-10+10+-5B*2+-1+-5B=

Simple and best practice solution for -10+10+-5B*2+-1+-5B= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10+10+-5B*2+-1+-5B= equation:


Simplifying
-10 + 10 + -5B * 2 + -1 + -5B = 0

Reorder the terms for easier multiplication:
-10 + 10 + -5 * 2B + -1 + -5B = 0

Multiply -5 * 2
-10 + 10 + -10B + -1 + -5B = 0

Reorder the terms:
-10 + 10 + -1 + -10B + -5B = 0

Combine like terms: -10 + 10 = 0
0 + -1 + -10B + -5B = 0
-1 + -10B + -5B = 0

Combine like terms: -10B + -5B = -15B
-1 + -15B = 0

Solving
-1 + -15B = 0

Solving for variable 'B'.

Move all terms containing B to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + -15B = 0 + 1

Combine like terms: -1 + 1 = 0
0 + -15B = 0 + 1
-15B = 0 + 1

Combine like terms: 0 + 1 = 1
-15B = 1

Divide each side by '-15'.
B = -0.06666666667

Simplifying
B = -0.06666666667

See similar equations:

| 4x-2+x=-2+2 | | 3(3x-8)=4x-6 | | 51x+18-29x=131 | | 8a-(1+5a)=4(3a-11)-24 | | 11b+4=37 | | 11x+8+17x-17=13x+79 | | m=m(c)2 | | 3m-1-6=13+7m | | w+2=-43-8t | | 28b^2-80b-12= | | 4x+35-15=9x-45 | | 3n+8=57 | | 1.8x+1.2x-5.4=-10 | | 2w(4w-1)=w(1-4w) | | 3(2x-1)=9x+3 | | 1a=-5a | | 0.08(x-100)=83.5-0.07 | | 3n+4=57 | | 5y+10-y=29 | | f(x)=x^2-4x-44 | | -8(v+7)+8=-33-5v | | Y+5-9=10 | | 2=2.27-4 | | 2*(5-3)-3x=5 | | 5(-4)-6-7(-4)=2 | | -7+-10P*2+-9(-10P*2+1)= | | (3y+100)+(y+80)=180 | | -5-15+1=14y-32-y | | -5x-2-10=2-(-2+4) | | 75-2x=-15 | | 16+2f=22 | | 2b+4=b-3 |

Equations solver categories